A rare cause of abdominal pain: Spontaneous rupture of the spleen - Odabaş, Esma Nilay; Topçuoğlu, Hazal; Aydoğan, Turabi; Özer, Vildan; Karaca, Yunus (Journal of Surgery and Medicine, 2021)
Spontaneous spleen rupture (SSR) has a high mortality rate, and numerous factors have been blamed in its etiology. In this case study, the purpose was to discuss a patient diagnosed with SSR in light of the literature. A 62-year-old male patient, who gave verbal permission to be presented in the case report, was admitted to the Emergency Service with abdominal pain, nausea, vomiting, and diarrhea complaints that started the day before. In the Focused Assessment with Sonography for Trauma (FAST) Ultrasonography (USG) of the patient, there was widespread free fluid in perihepatic and perisplenic areas. IV-contrasted abdominal computerized tomography (CT) revealed an unruptured saccular aneurysm in the left iliac artery, extravasation in the upper pole of the spleen, sub-capsular hematoma in the spleen, and widespread hemorrhagic fluid in the abdomen. The patient was diagnosed with rupture of the spleen and operated. It should be considered that patients applying to emergency services with abdominal pain and distension, with no trauma history, and anemia with no known cause in their examinations may have SSR.